About the weathering effect on sedimentary rocks organic matter - M. T. Delengov; N. P. Fadeeva; M. A. Bolshakova; E. V. Kozlova (Georesursy, 2024)
To get properties and characteristics of oil and gas source rocks and for other geological aims, geologists analyzes core samples from wells and outcrop samples. But we should probably somehow correct geochemical source rock properties data we get on outcrop samples, because organic matter could change significantly due to oxidizing and weathering. This problem is very important but poorly developed in modern publications, so it attracted our interest and led to this investigation. Published information on the organic matter weathering which change it’s content and quality in sedimentary rocks is collected and summarized in this article. The changes of the kerogen (isolated from the mineral matrix) elemental composition during its long-term storage are presented.We compared the results we get in laboratory and results of other authors who dealt with natural changes of organic matter in outcrops. An attempt to interpret the results obtained from the point of view of hypergene changes in OM was made. Uncertainties that require further study and development are indicated. This work is the first step to better understanding of weathering effect on organic matter content and properties – question of great importance for making adequate oil and gas prospects estimations.This study continues the work of our foregoers and Teachers – geochemists of the Petroleum Geology Department of Lomonosov Moscow State University: N.B. Vassoevich, Yu.I. Korchagina, O.A. Radchenko, V.A. Uspensky, I.E. Leifman, A.N. Guseva, O.K. Bazhenova, T.A. Kiryukhina.